Toward a refined classification of class I dithiol glutaredoxins from poplar: biochemical basis for the definition of two subclasses - Couturier, Jérémy; Jacquot, Jean-Pierre; Rouhier, Nicolas (Frontiers in Plant Science, 2013)
Glutaredoxins (Grxs) are small oxidoreductases particularly specialized in the reduction of protein-glutathione adducts. Compared to other eukaryotic organisms, higher plants present an increased diversity of Grxs which are organized into four classes. This work presents a thorough comparative analysis of the biochemical and catalytic properties of dithiol class I Grxs from poplar, namely GrxC1, GrxC2, GrxC3 and GrxC4. By evaluating the in vitro oxidoreductase activity of wild type and cysteine mutated variants and by determining their dithiol-disulfide redox potentials, pKa values of the catalytic cysteine, redox state changes in response to oxidative treatments, two subgroups can be distinguished. In accordance with their probable quite recent duplication, GrxC1 and GrxC2 are less efficient catalysts for the reduction of dehydroascorbate and hydroxyethyldisulfide compared to GrxC3 and GrxC4, and they can form covalent dimers owing to the presence of an additional C-terminal cysteine (CysC). Interestingly, the second active site cysteine (CysB) influences the reactivity of the catalytic cysteine (CysA) in GrxC1 and GrxC2 as already observed with GrxC5 (restricted to A. thaliana), but not in GrxC3 and C4. However, all proteins can form an intramolecular disulfide between the two active site cysteines (CysA-CysB) which could represent either a protective mechanism considering that this second cysteine is dispensable for deglutathionylation reaction or a true catalytic intermediate occurring during the reduction of particular disulfide substrates or in specific conditions or compartments where glutathione levels are insufficient to support Grx regeneration. Overall, in addition to their different sub-cellular localization and expression pattern, the duplication and maintenance along evolution of several class I Grxs in higher plants can be explained by the existence of differential biochemical and catalytic properties.